Preservation of foods - Fleming, Beulah (My University, 1904)
Introduction: The experiments, long ago, by Tyndall and Pasteur made it clear that fermentation and putrefaction are biological processes, the result of vital activities of living organisms, and not chemical action as hitherto been supposed. Like all living being the microorganisms of fermentation and putrefaction require conditions of temperature, moisture and food supply for the exercise of their vital activities. When we dry fruit by means of the evaporator, we simply prevent the action of ferment germs by cutting them off from needed moisture; in freezing meats the temperature is made too low for the existence of these agents of destruction; and in canning we by the aid of heat drive out the germs, and keep them out by hermetically sealing the cans.
Citation: Fleming, Beulah. Preservation of foods. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Preservation; Food; Food Preservation; Bacteria; Bacteria's Role in Food; Food Storage; Theses; Manuscripts (documents)